Exposure to traffic-related air pollution and the risk of developing breast cancer among women in eight Canadian provinces: A case–control study. (January 2015) - Hystad, Perry; Villeneuve, Paul J.; Goldberg, Mark S.; Crouse, Dan L.; Johnson, Kenneth; ,
Abstract: A few recent studies have reported positive associations between long-term exposure to traffic-related air pollution and the incidence of breast cancer. We capitalized on an existing Canadian multi-site population-based case–control study to further investigate this association. We used the National Enhanced Cancer Surveillance System, a population-based case–control study conducted in eight of 10 Canadian provinces from 1994 to 1997. A total of 1569 breast cancer cases and 1872 population controls who reported at least 90% complete self-reported addresses over the 1975–1994 exposure period were examined. Mean exposure levels to nitrogen dioxide (NO2 ) (an indicator of traffic-related air pollution) were estimated for this period using three different measures: (1) satellite-derived observations; (2) satellite-derived observations scaled with historical fixed-site measurements of NO2 ; and (3) a national land-use regression (LUR) model. Proximity to major roads was also examined. Using unconditional logistic regression, stratified by menopausal status, we estimated odds ratios (ORs) adjusted for many individual-level and contextual breast cancer risk factors. We observed positive associations between incident breast cancer and all three measures of NO2 exposure from 1975 to 1994. In fully adjusted models for premenopausal breast cancer, a 10 ppb increase in NO2 exposure estimated from the satellite-derived observations, the scaled satellite-derived observations, and the national LUR model produced ORs of 1.26 (95% confidence intervals (CIs): 0.92–1.74), 1.32 (95% CI: 1.05–1.67) and 1.28 (95% CI: 0.92–1.79). For postmenopausal breast cancer, we found corresponding ORs of 1.10 (95% CI: 0.88–1.36), 1.10 (95% CI: 0.94–1.28) and 1.07 (95% CI: 0.86–1.32). Substantial heterogeneity in the ORs was observed across the eight Canadian provinces and reduced ORs were observed when models were restricted to women who had received routine mammography examinations. No associations were found for road proximity measures. This study provides some support for the hypothesis that traffic-related air pollution may be associated with the development of breast cancer, especially in premenopausal women. With the few studies available, further research is clearly needed. Highlights: Breast cancer incidence was associated with exposure to nitrogen dioxide air pollution. Associates were largest for premenopausal breast cancer. Associates varied by study province and mammography screening history.